Climate crisis and indigenous technologies in the Amazon: a study on the resilience and adaptation of the Ticuna and Marubo peoples: Climate crisis and indigenous technologies in the Amazon: a study on the resilience and adaptation of the Ticuna and Marubo peoples (Revista de História da UEG (REVHIST), 2025)
This paper investigates how the Ticuna and Marubo Indigenous peoples, located in the Alto Solimões region of the Brazilian Amazon, have been facing the impacts of the climate crisis through ancestral practices and traditional technologies for caring for the land, forest, and rivers. The research is grounded in the fields of Environmental History and the History of the Anthropocene, weaving together Indigenous and academic knowledge to understand these peoples' strategies of adaptation and resistance in the face of increasingly extreme climate events such as droughts, wildfires, and shortages of food and water. Through the analysis of oral narratives, documents, and community experiences, the study highlights how Indigenous cosmologies offer concrete alternatives to the dominant developmentalist and extractivist logic. By recognizing the value of Indigenous epistemologies, the paper points to the urgency of public policies that engage with these knowledges and to the need for climate justice that is simultaneously social, territorial, and epistemic.Keywords: Indigenous peoples; Amazon; Climate crisis; Traditional technologies; Environmental History.